Ashirwad: An extremely cost efficient Swabbing Robot (International Journal of Engineering and Computer Science, 2017)
This swabbing robot is highly beneficial for cleaning purpose especially in homes, Offices, Industries where cleanliness is a major concern. Many research organizations are busy finding the best outcomes through the artificial intelligence. Of course, Artificial intelligence is a branch of technology that makes computers thinks like human brain. This device will sweep, and mop the floor area with brush and other wiping components; also it collects the dust and other small parts in it. Mapping is used to instruct the moment of this mini device. The device is too easy to use, very cost effective and cleans every corner of the area. Being autonomous, it would work in your absence